Talent identification and development tools. (10th June 2014) - Natacha Golik, Mariela; Rita Blanco, María
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to contribute to talent management literature by examining empirically the relationship between talent identification and development tools. Design/methodology/approach – The study sample consisted of 112 Argentina-based companies. All participants completed an online survey containing a list of identification and development practices. Responses were analyzed with SPSS 19. Findings – Results show that companies running more talent identification processes (performance management and potential identification) make use of a greater number of development tools. Significant differences were observed in the use of all development tools analyzed, with the exception of formal education and job rotation. Results indicate that the presence of a Development Department encourages the implementation of identification and development tools. Practical implications – The study suggests that the better the quality of the information involved during the identification stage, the higher the contribution to development investment decisions. Companies should do well to rely on higher-quality diagnostic information to facilitate a better selection of development tools to fulfill specific objectives. The existence of a Development Department favors the implementation of a greater number of identification and development tools. Originality/value – This paper adds to fill a perceived gap in the literature investigating, empirically, the relationship between talent identification processes and development tools.